Supervising in English: The Doctoral Thesis, Professor/Student Discourse, and Social Practice - Mattisson, Jane (Respectus Philologicus, 2014)
My article investigates the situation, goals, and discourse praxis of professors supervising doctoral students writing in English. It is part of a wider project examining student-teacher interaction which is designed to improve written communication, particularly at the higher levels of academic study. Like the students they supervise, the five professors studied are English as a Foreign Language users, and all give instruction exclusively in English. Based on separate interviews with each professor, my study demonstrates that there is a tendency among doctoral supervisors to focus on the content and form of the thesis to the detriment of socio-cultural practice, i.e., the discourse between the professor and student, as well as the recognition of the text as a piece of social practice, shaped by a particular kind of academic public and the rules of scholarship that have been developed over time. The type of social practice that students bring with them varies from culture to culture. I argue that a doctoral thesis bears witness not only to the student’s ability to conduct research at a high level, but also to the creation of a distinct scholarly identity that is the result of effective discourse between professor and student, whereby the professor communicates “the rules of the game” that lead to a successful career both at university and after. My paper reflects on how we as teachers/supervisors can promote the formation of scholarly identity through the medium of English as a Foreign Language. I do so by focusing on the five supervisors’ knowledge of English, their ability to provide guidance in English, and their awareness of the importance of promoting scholarly identity in English. The article concludes with some reflections on the type of support required, if any, from native English teachers.